Emerging polycentric city-regions in Germany. Regionalisation of economic activities in metropolitan regions - Growe, Anna (ERDKUNDE, 2012)
Over the last decades the hierarchical understanding of the relationship between cities and their hinterlands has been replaced by a network-based understanding. In the context of this development, the emergence of polycentric network structures in urban regions is discussed, with a focus on qualitative changes in the relationship between cities and their hinterlands. This paper analyses the extent to which the emergence of polycentric regions can be observed in the German urban system. Using commuting data and employment data with a focus on knowledge-based services it is analysed what centres besides core cities are becoming primary hubs to enable processes of regionalisation in three metropolitan regions in Germany. The results indicate that, in spite of an affinity of knowledge-based services to core cities, processes of regionalisation can also be observed with these activities. However, due to the importance of transaction costs a location in other cities in polycentric regions can be expected to be more attractive than a location in the suburbanised or rural hinterland.